1997
DOI: 10.1111/j.1600-0781.1997.tb00227.x
|View full text |Cite
|
Sign up to set email alerts
|

How well are sunscreen users protected?

Abstract: Previous studies have shown that people often apply less sunscreen than the recommended amount of 2 mg/cm2. Our purpose in this study was to determine objectively how photoprotection varies with application thickness. The protection provided by differing quantities of sunscreens containing varying amounts of titanium dioxide was measured in vitro using excised human epidermis as the substrate. It was found that application thickness had a significant effect on the sun protection factor (SPF), with most users p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 8 publications
0
76
1
1
Order By: Relevance
“…It has been argued that sunscreen should be reapplied 15 to 30 minutes after exposure begins because it is frequently applied nonuniformly and in insufficient amounts to achieve the rated SPF. 47 Previously, sunscreens with an SPF of 15 were considered acceptable; however, because consumers typically apply sunscreens thinly, 48 and because sunscreens with an SPF of 30 or higher are now widely available, their use is recommended. 49 It is important that sunscreen be considered only part of an overall sun protection strategy, because users are still susceptible to the deleterious effects of excessive sunlight exposure.…”
Section: Prevention and Early Diagnosismentioning
confidence: 99%
“…It has been argued that sunscreen should be reapplied 15 to 30 minutes after exposure begins because it is frequently applied nonuniformly and in insufficient amounts to achieve the rated SPF. 47 Previously, sunscreens with an SPF of 15 were considered acceptable; however, because consumers typically apply sunscreens thinly, 48 and because sunscreens with an SPF of 30 or higher are now widely available, their use is recommended. 49 It is important that sunscreen be considered only part of an overall sun protection strategy, because users are still susceptible to the deleterious effects of excessive sunlight exposure.…”
Section: Prevention and Early Diagnosismentioning
confidence: 99%
“…The SPF protection afforded may be reduced due to inadequate application (<2 mg/cm 2 ), water resistance, and abrasion from clothing and/or sand (12,13). Several studies have found that consumers apply much less than this recommendation (14 -16), providing a level of protection 20% to 50% less than that stated by the SPF (17).…”
Section: Introductionmentioning
confidence: 99%
“…Human exposure levels to nano-TiO 2 from personal care products, including sunscreens, toothpastes, and cosmetics, are unknown. However, nano-TiO 2 levels as high as 90 mg per mg of lotion have been found in certain sunblocks (Weir et al, 2012) that, if applied at the recommended density of 2 mg lotion per cm 2 exposed skin (Stokes & Diffey, 1997) could result in exposures of 24 mg/kg per application for a 60 kg individual applying the lotion to half of their body surface area.…”
Section: Discussionmentioning
confidence: 99%